+0  
 
0
39
1
avatar

https://latex.artofproblemsolving.com/c/b/1/cb111da0c0b3bb7356acf6ba2e82cc76465d96a3.png

Guest Dec 29, 2017
Sort: 

1+0 Answers

 #1
avatar+80905 
+2

(r + 3)  / ( r - 2)   =  (r - 1)  / ( r + 1)      cross-multiply

 

(r + 3) ( r + 1)  =  (r - 2) (r - 1)     simplify

 

r^2 + 4r  +  3   =   r^2 - 3r  +  2         subtract r^2 from both sides

 

4r + 3   =    -3r  +  2           add 3r to both sides, subtract 3 from both sides

 

7r  =  - 1       divide both sides by 7

 

r  =  - 1/7

 

 

cool cool cool

CPhill  Dec 29, 2017

30 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details